Genome-Wide Regulatory Network Mapping of miRNA and Transcription Factors in Banana Roots - Gudimella, Ranganath; Singh, Pooja; Mazumdar, Purabi; Wong, Gwo Rong; Lau, Su Ee; Harikrishna, Jennifer Ann (Springer Verlag, 2018)
MicroRNA (miRNA) are important regulators of gene expression. Plant miRNA have been reported both to target and to be regulated by transcription factors, however, genomic distribution of miRNA, transcription factor targets for miRNA, transcription factor binding sites (TFBS) of miRNA promoters and their regulatory networks have not been systematically mapped in banana. In this study, genome-wide annotation of miRNA in the most recently published banana genome sequence was used to predict miRNA promoter regions and to map TFBS of miRNA genes. A total of 183 mature miRNAs, comprising 144 orthologous miRNA and 39 Musa-specific miRNA were predicted. Following this, banana root degradome data was used to confirm miRNA targets and the transcription factor targets were placed into a predicted network together with their targeting miRNA using cytoscape. Gene ontology of the 20 transcription factors among the predicted miRNA targets, showed predominance for auxin-activated signalling and developmental processes. Profiling of TFBS motifs across miRNA promoter regions showed that binding site motifs for TCP, AP2/ERF, GATA, NF-YB, DOF, B3, bZIP, trihelix, ZF-HD, bHLH and Dehydrin transcription factor families are abundant in the Musa acuminata genome. Finally, we propose a regulatory network for the miRNA families miR156, miR164, miR166, miR171, miR319, miR396, miR528, mac-miR-new14 and mac-miR-new20 and their respective transcription factor targets.